The Risk Factors of Anorectal Malformation Patients Mortality in Palembang - Muhammad Bima; Shalita Dastamuar; Rachmat Hidayat (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2018)
Anorectal malformations are serious anal and rectal disorders ranging from stenosis to anorectal agenesis. The incidence of mortality in cases of anorectal malformations is influenced by many factors, including the type of anorectal malformation, associated congenital anomalies, sepsis, and prematurity as investigated in this study. The aim of this study was to identify the risk factor of mortality on anorectal malformation patients. This study is an observational analytic study with cross sectional study design. Secondary data collection was obtained from eighty-two medical records of anorectal malformation patients in Dr. Mohammad Hoesin Hospital Palembang from January 2015 to June 2017 that meets the inclusion criteria. From eighty-two cases of anorectal malformations found nineteen cases of mortality (23.2%). There were four risk factors identified, anorectal malformation type, associated congenital anomalies, sepsis, and prematurity. Two risk factors found significantly affect the mortality on anorectal malformation patients, anorectal malformation type (p value = 0.036) and sepsis (p value = 0.049) from four risk factors studied. Type of anorectal malformation and sepsis have a significant effect on the mortality of patients with anorectal malformations, but there is no effect on the mortality of the patients with assciated congenital anomalies and prematurity. Keywords: Anorectal malformation, congenital abnormalities, sepsis, prematurity